Anti-anthropomorphism and Its Limits - Bruni, Domenica; Perconti, Pietro; Plebe, Alessio (Frontiers in Psychology, 2018)
There is a diffuse sentiment that to anthropomorphize is a mild vice that people tend to do easily and pleasingly, but that an adult well educated person should avoid. In this paper it will be provided an elucidation of ``anthropomorphism'' in the field of common sense knowledge, the issue of animal rights, and about the use of humans as a model in the scientific explanation. It will be argued for a ``constructive anthropomorphism'', i.e., the idea that anthropomorphism is a natural attutude to attribute human psychological features to other individuals, no matter they are actually rational agents, or not. If we know the ``grammar'' of this attutude, we can avoid the risks in overestimating the environmental inputs towards anthropomorphism and, at the same time, take the heuristic advantages of anthropomorphism in the use of human mind as a model for both everyday circumstances and scientific enterprise.